The price of federalism - Peterson, Paul E. (Brookings Institution, 1995)
What level of government should be responsible for welfare, education, transportation, and other programs? What are the proper roles of the local, state, and national government? What price do we pay for our federal system? Does federalism perpetuate social inequality? Does it stifle economic growth? More intensely than ever, these questions are at the center of ongoing debate in Congress, statehouses, and town meetings. In this important book, Paul E. Peterson, one of the nation's leading experts on urban problems and American government, addresses them by bringing together two theoretical perspectives on federalism: functional and legislative. He uses these perspectives to explain the changes in federalism that have occurred over the past thirty-five years and to examine the proposals included in the Republican "Contract with America."